Ultrasonic Vocalizations of Male Mice Differ among Species and Females Show Assortative Preferences for Male Calls - Musolf, Kerstin; Meindl, Stefanie; Larsen, Angela L.; Kalcounis-Rueppell, Matina C.; Penn, Dustin J. (PloS one, 2015)
Male house mice (Mus musculus) emit ultrasonic vocalizations (USVs) during courtship, which attract females, and we aimed to test whether females use these vocalizations for species or subspecies recognition of potential mates. We recorded courtship USVs of males from different Mus species, Mus musculus subspecies, and populations (F1 offspring of wild-caught Mus musculus musculus, Mus musculus domesticus (and F1 hybrid crosses), and Mus spicilegus), and we conducted playback experiments to measure female preferences for male USVs. Male vocalizations contained at least seven distinct syllable types, whose frequency of occurrence varied among species, subspecies, and populations. Detailed analyses of multiple common syllable types indicated that Mus musculus and Mus spicilegus could be discriminated based on spectral and temporal characteristics of their vocalizations, and populations of Mus musculus were also distinctive regardless of the classification model used. Females were able to discriminate USVs from different species, and showed assortative preferences for conspecific males. We found no evidence that females discriminate USVs of males from a different subspecies or separate populations of the same species, even though our spectral analyses identified acoustic features that differ between species, subspecies, and populations of the same species. Our results provide the first comparison of USVs between Mus species or between Mus musculus subspecies, and the first evidence that male USVs potentially facilitate species recognition.